2001
DOI: 10.1128/mcb.21.17.5723-5732.2001
|View full text |Cite|
|
Sign up to set email alerts
|

HMG Box Transcriptional Repressor HBP1 Maintains a Proliferation Barrier in Differentiated Liver Tissue

Abstract: We previously isolated HBP1 as a target of the retinoblastoma (RB) and p130 family members and as the first of the HMG box transcriptional repressors. Our subsequent work demonstrated that HBP1 coordinates differentiation in cell culture models. In the present study, we show that HBP1 regulates proliferation in a differentiated tissue of an animal. Using transgenic mice in which HBP1 expression was specifically increased in hepatocytes under control of the transthyretin promoter, we determined the impact of HB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 49 publications
4
52
0
Order By: Relevance
“…The repression of ligandinduced receptor activation was previously reported for corepressor complexes coordinated by the SMRT/HDAC1-associated repressor protein (SHARP) (34), the transcription intermediary factor TIF1 (35), and the metastases-associated protein 1 co-repressor MTA (36). The binding of cyclin D1 to HDAC1 and the inhibition of PPAR␥-mediated differentiation by cyclin D1 is also consistent with previous studies on the role of HDAC1 in regulation of nuclear receptor function (30).…”
Section: Versus 2) Increased Hdac Recruitment In Cyclin D1supporting
confidence: 78%
“…The repression of ligandinduced receptor activation was previously reported for corepressor complexes coordinated by the SMRT/HDAC1-associated repressor protein (SHARP) (34), the transcription intermediary factor TIF1 (35), and the metastases-associated protein 1 co-repressor MTA (36). The binding of cyclin D1 to HDAC1 and the inhibition of PPAR␥-mediated differentiation by cyclin D1 is also consistent with previous studies on the role of HDAC1 in regulation of nuclear receptor function (30).…”
Section: Versus 2) Increased Hdac Recruitment In Cyclin D1supporting
confidence: 78%
“…Most of our previous works focused on its transcriptional repression and regarded HBP1 as a novel transcriptional repressor in differentiation (Tevosian et al, 1997;Shih et al, 1998Shih et al, , 2001Lemercier et al, 2000;Xiu et al, 2003;Smith et al, 2004;Paulson et al, 2007). Only few studies have reported that HBP1 is a transcriptional activator in myeloid differentiation and transformation (Lavender et al, 1997;Yao et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Then, cells were incubated overnight at 37 1C with freshly prepared SA-b-gal stain solution (1mg/ml X-gal, 40 mM citric acid/sodium phosphate (pH 6.0), 5 mM potassium ferrocyanide, 5 mM potassium ferricyanide, 150 mM NaCl, 2 mM MgCl 2 ). At least 300 cells were counted in randomly chosen fields (Shih et al, 2001).…”
Section: Immunoblots and Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…16 In several models of impaired liver regeneration, cyclin D1 expression after PH is diminished. [18][19][20][21][22] Cyclin D1 is dependent on mitogen stimulation in cultured hepatocytes, and its induction during late G1 phase coincides with progression through the late G1 restriction point, at which time the cell becomes committed to proceed with replication even if mitogens are withdrawn. 23,24 Furthermore, transfection of hepatocytes in culture with cyclin D1 promotes cell cycle progression in the absence of mitogen, or in the presence of growth-inhibitory extracellular matrix (ECM) conditions.…”
mentioning
confidence: 99%